Titanic : young survivors - Zullo, Allan (Zullo, Allan. Ten true tales., 2012)
Presents ten true tales of young survivors of the 1912 Titanic shipwreck, including seventeen-year-old Jack Thayer, fifteen-year-old Edith Brown, and eleven-year-old Billy Carter.